KAJIAN BEBERAPA MEDIUM PENYERAP KMNO4 DAN SUHU TERHADAP PENYAKIT ANTRAKNOSA PADA PISANG KULTIVAR SUSU LEPAS PANEN KEMASAN PLASTIK POLIETILEN - AFGANI, RONY AL; SOESANTO, LOEKAS; SRI UTAMI, DARINI (Agrotrop : Journal on Agriculture Science; Vol 1 No 2 (2011))
Study of Several KMnO4 Absorbant Media and Temperature on Antracnose of Postharvest Susu Cultivar Banana Packaged in Polyethylene Plastic. A research was aimed to know the best KMnO4 absorbant media, temperature, and their combination on antracnose of postharvest susu cultivar banana packaged in polyethylene plastic was carried out at the Laboratory of Plant Disease, Faculty of Agriculture, Jenderal Soedirman University, Purwokerto. The banana with age of 3.5 months after flowering was taken from Sokawera Village, Somagede District, Banyumas Regency, Central Java. Split-Plot Design was used with the plastic. The main plot was room (25-28oC) and low (15-17oC) temperatures. The sub plot was without media and with or without inoculation, media of charcoal, coal, brick, cotton, and rockwool. Variable observed was incubation period, attact area, attact intensity, waste index, softy rate, and sugar content. Result of the research showed that the best media for absorbing KMnO4 was cotton. Low temperature could decrease softy rate of 64.75% and attact area of 92.78% compared to room one. Combination between cotton or rockwool and without inoculation at low temperature was the best treatment because of decreasing attact area ofColletotrichum musae and waste index for 100%. Inoculation of the fungus was not affect fungus attact in the KMnO4 and its combination with temperature. All treatments were not affect colour, aroma, and taste of the banana.
Keywords: antracnose, postharvest susu banana, KMnO4 absorbant media, temperature